2018
DOI: 10.1128/msphere.00137-18
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Comparative Genomics of F33:A−:B− Plasmids Carrying bla CTX-M-55 or bla CTX-M-65 in Escherichia coli and Klebsiella pneumoniae Isolated from Animals, Food Products, and Humans in China

Abstract: Worldwide spread of antibiotic resistance genes among Enterobacteriaceae isolates is of great concern. F33:A−:B− plasmids are important vectors of resistance genes, such as blaCTX-M-55/-65, blaNDM-1, fosA3, and rmtB, among E. coli isolates from various sources in China. We determined and compared the complete sequences of 17 F33:A−:B− plasmids from various sources. These plasmids appear to have evolved from the same ancestor by mobile element-mediated rearrangement, acquisition, and/or loss of resistance modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 36 publications
(42 reference statements)
2
38
0
Order By: Relevance
“…The type K genetic structure in pHNBC6-3 (F33:A-:B-) showed 99% nucleotide identity to that found in our previously described pHNMC02 F33:A-:B- plasmid ( MG197489 , chicken, E. coli ) and pHNGD4P177 ( MG197492 , pig, E. coli ) ( 24 ) and differed by only three nucleotide changes. The resistance region was bound by fragments of ΔIS 1 and contained four IS 26 elements flanking three different segments associated with a fosA3 resistance module ( Fig.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…The type K genetic structure in pHNBC6-3 (F33:A-:B-) showed 99% nucleotide identity to that found in our previously described pHNMC02 F33:A-:B- plasmid ( MG197489 , chicken, E. coli ) and pHNGD4P177 ( MG197492 , pig, E. coli ) ( 24 ) and differed by only three nucleotide changes. The resistance region was bound by fragments of ΔIS 1 and contained four IS 26 elements flanking three different segments associated with a fosA3 resistance module ( Fig.…”
Section: Resultssupporting
confidence: 57%
“…In our study, fosA3 was found to be responsible for fosfomycin resistance in ESBL-producing Enterobacterales strains from vegetables. fosA3 has been detected in many countries around the world but mainly occurs in E. coli from food animals in China ( 5 , 10 , 24 27 ). However, there are very few related reports on vegetable sources, with only one related study on fosA3 (1.2%) in ESBL-producing E. coli isolates in Germany reported recently ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids play a critical role in the global dissemination of ESBL genes . The bla CTX-M-55 gene was frequently found on IncF, IncI1, and IncHI2 plasmids of E. coli in many countries, including China (Yang et al, 2014;Wang et al, 2018), France (Lupo et al, 2018), and United States (McGann et al, 2016). Similarly, the presence of I1-Iγ, F, and P plasmids in bla CTX-M-55 -positive ESBL-EC isolates from pigs has been documented in South Korea (Tamang et al, 2013b).…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, additional results have confirmed relatively high genomic correlation between Sc. and Lm., further supporting a high degree of relatedness based on both sequence homology and evolutionary history 44 . Here, comparative genomics was conducted to comprehensively analyze the relationship between Sc.…”
Section: Comparative Genomics Analysismentioning
confidence: 64%